University teachers’ perspectives on the use of mother tongue in ELT (Scholars' Journal, 2020)
The use of mother tongue (L1) in teaching English has always been a debatable issue as there are multiple opinions of the teachers regarding it. They are not sure to either use mother tongue in English language teaching or avoid it for effective teaching. The primary purpose of this phenomenological study of qualitative research was to find out the university teachers' perception on the use of mother tongue along with their effectiveness of L1 use at undergraduate level of Far Western University in Nepal. The participants of this study were four English language teachers teaching in the same university having more than ten years of teaching experience. The researcher used semi-structured interview and classroom observation for collecting data. The findings demonstrated that most of the teachers supported the judicious use of mother tongue in English language teaching classes based on their own experiences. The study also showed that overuse of L1 in second language (L2) classes might have some harm. It concludes that judicious use of L1 is a better way to deal with the students having poor proficiency in English language and enhance students' participation. The study recommends that teachers can make use of the students’ mother tongue purposefully whenever they think it is necessary to do in their classes.